SUBHORIZONTAL GEODYNAMIC ACTIVE ZONES AT THE PLATFORMS - METHODS OF IDENTIFICATION AND EVALUATION - V. M. Makeev; E. A. Karfidova; I. V. Korobova (Известия высших учебных заведений: Геология и разведка, 2016)
Authors developed a geoinformation(GIS) method considering the degree of disagreement between the key horizons of the different ages for the detection and evaluation of the subhorizontal geodynamic active zones at the platforms. The method is based on the analysis of the digital elevation models and the model of detection of the azimuthal and angular displacements zones. The allocation graphics of these zones indicate a heterogeneous structure of the key horizons, which is the reason for the development of subhorizontal geodynamic active zones. It is assumed, the greater the disagreement between the surfaces of the different age, the higher the probability of the development of the zones which might be dangerous by causing the activation of geological processes.